A crystal plasticity representative volume element model for simulating nanoindentation of aluminium alloy 2024 - Li, L.; Shen, L.; Proust, G.; Loo Chin Moy, Charles; Ranzi, G. (ICCM2012, 2012)
Three-dimensional crystal plasticity (CP) finite element simulations are performed to study the mechanical response of aluminium alloy 2024 under nanoindentation. To improve computational efficiency, a grain-scale representative volume element (RVE) with periodic boundary conditions is adopted to represent the global response of macro-scale tests. The parameters of the CP constitutive model are calibrated using tensile tests performed on the aluminium at 0, 45 and 90 degrees from the rolling direction. The initial grains which are statistically consistent with our experimental observations are created using Voronoi tessellation method, and the grain orientations are obtained from electron back-scatter diffraction test. Four depths of nanoindentation are simulated using a CPRVE and elasto-plastic combined model, and indentation moduli are calculated and compared with the Young’s modulus obtained from experiments. It appears from the simulation results that the proposed CPRVE model can reproduce the mechanical response of specimens subjected to local large deformation induced by nanoindentation, and help understand the interaction among adjacent grains with different orientations. Moreover, the proposed model is capable of producing misorientation maps which capture the crystal deformation in the indentation zone.